Analysis of Factors Related to Referral Cases in Childbirth - Yulyati, Iis; Yuliwati, Nanik (Indonesian Journal of Global Health Research, 2024)
Various factors can affect the number of referrals and the quality of referrals. This increase in referral rate can be an indication that the implementation of the referral system has not gone well. These indicators can be divided into indicators from the midwife's side, namely education and length of work, and indicators from the family in the form of support provided and speed of decision making. The purpose of this study was to analyze the effect of midwife education, midwives' tenure, and family support on referral success. This study is a type of intervention research with a cross sectional design. The location used for this study is at the Cikande Health Center in November-December 2023. The samples used in this study, using total sampling with samples were 30 obstetric referral cases. The data was collected by questionnaire. The independent variables were midwives' education, midwives' length of service, and family support. The dependent variable is referral success. The test used is the Chi Square test. The results of p value 0.007 < 0.05 which indicate that education has a significant relationship with referral success, p value 0.023 < 0.05 which indicates that midwives' tenure has a significant relationship with referral success, and p value 0.001 < 0.05 which indicates that the support provided by family has a very significant relationship with referral success.